Rumah Inti untuk Percepatan Rehabilitasi dan Rekonstruksi Pasca Bencana bagi Masyarakat Pedesaan - Agam Marsoyo (Unisia, 2007)
The core house as instead of the tent in rehabilitation and reconstruction process for villagers who have undergone natural disasters is needs so that they can return to normal life and they have a good future. The recovery process of the core house after disaster actually is not easy inparticular because of the limited fund resources. Thus, it needs to be capitalized by the other capital resources in that process, for instance social capital. The core house building and trnsforming in the villagers area needs community who have social capital to accelerate its existence.